The Hardware Trojan War Attacks, Myths, and Defenses - Bhunia, Swarup; Tehranipoor, Mark M. (Springer International Publishing : Imprint: Springer, 2018)
This book, for the first time, provides comprehensive coverage on malicious modification of electronic hardware, also known as, hardware Trojan attacks, highlighting the evolution of the threat, different attack modalities, the challenges, and diverse array of defense approaches. It debunks the myths associated with hardware Trojan attacks and presents practical attack space in the scope of current business models and practices. It covers the threat of hardware Trojan attacks for all attack surfaces; presents attack models, types and scenarios; discusses trust metrics; presents different forms of protection approaches - both proactive and reactive; provides insight on current industrial practices; and finally, describes emerging attack modes, defenses and future research pathways.